'The best app is the teacher' Introducing classroom scripts in technology‐enhanced education. (21st February 2017) - Montrieux, H.; Raes, A.; Schellens, T.
Abstract: A quasi‐experimental study was set up in secondary education to study the role of teachers while implementing tablet devices in science education. Three different classroom scripts that guided students and teachers' actions during the intervention on two social planes (group and classroom level) are compared. The main goal was to investigate which classroom script leads to the best results regarding progress in domain‐specific knowledge and inquiry skills. Besides student achievement, students' experiences towards the role of the teacher and students' perceptions towards learning with tablets within the three conditions were investigated. In the first condition, the classroom script included learning activities that were balanced between the group and the classroom level. In the second condition, the learning activities occurred predominantly on the group level. The third condition entailed the classroom script as the control condition in which the learning activities were situated only on the classroom level, with the tablet used in a traditional way or as 'book behind glass' . Results show that students perform better on domain‐specific knowledge in the conditions where the teacher intervened on the classroom level. Regarding the acquisition of inquiry skills, students performed best in the condition where the learning activities were balanced between the group and the classroom level. Moreover, students who perceived more structure achieved better. These results indicate that the role of the teacher cannot be ignored in technology‐enhanced learning. Moreover, these results seem to suggest that one of the best apps remains the teacher. Lay description: What is currently known about the subject matter Empirical research on the impact of tablet devices is limited. Teachers play a pivotal role when it comes to technology integration in the classroom. Empirical research focusing on how teachers should be supported while using tablet devices is lacking. What this paper adds This study, embedded in an authentic context, studied the role of teachers using classroom scripts while implementing tablet devices. This empirical research focused on the impact of classroom scripts on domain‐specific knowledge, inquiry learning and on student perceptions while using tablet devices during science education. Implications of study findings for practitioners Results show that besides the way tablet devices are implemented, it remains the teacher who determines the success of learner‐centred learning with tablets. This study shows that in spite of tablet devices' potential to promote learner‐centred learning, students reported the need of plenary teacher‐led class interventions. Putting forward a classroom script can be helpful to guide teachers to orchestrate the use of tablets during science education.